'We are such stuff': Shakespeare and material culture in eighteenth-century England - Myers, Anna S. (The University of Edinburgh, 2024)
Adopting a material culture lens, this thesis investigates the social and cultural history of William Shakespeare over the course of the long eighteenth century in England. As the period during which Shakespeare ascended to the status of English national poet, the subject has received a substantial amount of scholarly attention. This body of research, however, has primarily been rooted in the review of literary and visual cultures and has rarely transcended strict disciplinary boundaries. While building on these studies, this thesis departs from previous scholarship to centre on material culture and notions of materiality. It takes interdisciplinarity as a conceptual starting point, working principally between the fields of history of art and English literature to scrutinise a community of objects decorated with or derived from images of Shakespeare or his plays alongside visual and literary sources. In doing so it hopes to contribute a more profound understanding of the extent to which the eighteenth-century English populace engaged with Shakespeare and his literary corpus and their conceptions of England’s national poet. Collectively the four chapters presented in this thesis interrogate the ‘things’ that mediated contemporary material encounters with Shakespeare and his literary corpus. Chapter 1 examines the history of a mulberry tree believed to have been planted by Shakespeare circa 1609 at Stratford-upon-Avon and the perception of objects carved from its wood as ‘relics’. A discussion of sensory encounters with ‘Shakespeare mulberry relics’ demonstrates the significance of physical contact to eighteenth-century conceptions of Shakespeare and broader social and national narratives. Chapter 2 evaluates the significance of ‘material adaptations’. It scrutinises the adaptation of Shakespeare’s play Richard III over the course of the eighteenth century and across media – from play text and performance to visual and material culture – establishing the legibility of Richard III as a cautionary tale of a tyrannic king while traversing mediums and spaces. The chapter argues that as a material adaptation, Richard III stimulated personal and communal reflections on civil notions such as morality and virtue. Considering printed fans and snuff boxes ornamented with images of Shakespeare’s plays, Chapter 3 analyses the significance of the aesthetic properties of these objects to gendered social exchanges. The chapter illustrates how Shakespeare, or his literary corpus, could be invested in the extra linguistic ‘language’ of the fan and ritual of snuff-taking, and were therefore constituent to interpersonal and self-expressive processes. Finally, Chapter 4 examines interior decorations and furnishings demonstrating how Shakespeare, and his works, could be employed within domestic spaces to express and constitute an individual’s sense of English identity. It adopts As You Like It as a case study, analysing the play’s manifestation in visual and material culture and exploring the play’s representation as a furnishing textile. Ultimately, this thesis presents a novel methodological approach to evaluate the social and cultural history of Shakespeare in the long eighteenth century by embracing material culture and interdisciplinarity as modes of historical inquiry. Accordingly, it seeks to illuminate the expanse of cultural fabrications and societal structures informed and inhabited by Shakespeare, from selfhood and communal identities to social status and gendered relations.
Keywords: William Shakespeare; eighteenth-century England; history of art; mulberry tree; material adaptatons; Richard III; English identity; social and cultural history